2021
DOI: 10.1016/j.dci.2020.103848
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic differences in the innate response after immune stimulation during zebrafish sex differentiation

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 82 publications
0
5
0
Order By: Relevance
“…Another environmental factor, the density—the number of fishes in a tank—, caused masculinization in zebrafish [ 97 ] revealing some epigenetic alterations in the fish gonads [ 98 ]. Additionally, environmental-epigenetics interactions after immune stimulation during sex differentiation in zebrafish showed an alteration of the methylation of some immune-related genes [ 99 , 100 ]. The present data indicated that the epigenetic machinery was reprogrammed by gravity alterations, and although much data needs to be performed, particularly whether zebrafish would be used as a space-related animal model, the underlying epigenetic alterations need to be considered to fully comprehend the gravity-epigenome interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Another environmental factor, the density—the number of fishes in a tank—, caused masculinization in zebrafish [ 97 ] revealing some epigenetic alterations in the fish gonads [ 98 ]. Additionally, environmental-epigenetics interactions after immune stimulation during sex differentiation in zebrafish showed an alteration of the methylation of some immune-related genes [ 99 , 100 ]. The present data indicated that the epigenetic machinery was reprogrammed by gravity alterations, and although much data needs to be performed, particularly whether zebrafish would be used as a space-related animal model, the underlying epigenetic alterations need to be considered to fully comprehend the gravity-epigenome interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Another environmental factors, the density —the number of fishes in a tank—, caused masculinization in zebrafish (Ribas, Valdivieso, et al, 2017) revealing some epigenetic alterations in the fish gonads (Caballero, unpublished results). Additionally, environmental-epigenetics interactions after immune stimulation during sex differentiation in zebrafish showed and alteration of the methylation of some immune-related genes (Caballero-Huertas et al, 2020; Moraleda-Prados et al, 2021). The present data indicated that the epigenetic machinery was reprogrammed by gravity alterations, and although many data needs to be performed, in particularly whether zebrafish would be used as a space-related animal model, the underlying epigenetic alterations need to be considered to fully comprehend the gravity-epigenome interactions.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, head kidney is considered the principal immune organ in fish (Rauta et al 2012) and it is developed from larval pronephros, where also P. neurophilia presence has been recorded (Figure 2a) (Sanders et al 2014). Moreover, pronephros has been recently described as a location where lipopolysaccharide (LPS) is recruited after bath immune stimulation in zebrafish larvae (Moraleda-Prados et al, 2021). Therefore, future studies on both head kidney and pronephros roles in P. neurophilia infections are of interest to cope with the disease by developing immunity.…”
Section: Target Organs For Pseudoloma Neurophilia Infestationmentioning
confidence: 99%
“…2014). Moreover, pronephros has been recently described as a location where lipopolysaccharide (LPS) is recruited after bath immune stimulation in zebrafish larvae (Moraleda‐Prados et al, 2021). Therefore, future studies on both head kidney and pronephros roles in P. neurophilia infections are of interest to cope with the disease by developing immunity.…”
Section: Target Organs For Pseudoloma Neurophilia Infestationmentioning
confidence: 99%
See 1 more Smart Citation